Coronary atherosclerosis burden by coronary computed tomography in type II diabetes with preclinical non-obstructive carotid atherosclerosis and without inducible myocardial ischemia. (January 2017) - Palmieri, Vittorio; Gravino, Enzo; Russo, Cesare; Salvati, Armenio; Lombardi, Carmelo; Sauro, Rosario; Rosato, Giuseppe
Highlights: Persons with type II diabetes require stringent cardiovascular risk factors control. However, methods for identification of a specific phenotype candidate to aggressive cardiovascular risk factors control among asymptomatic persons with type II diabetes is controversial. Carotid atherosclerosis is an independent predictor of cardiovascular events, but those without inducible myocardial ischemia are thought to be at low cardiovascular risk even in the presence of type II diabetes. Coronary artery calcium is an independent predictor of cardiovascular events, but computed tomography for assessment of coronary artery disease burden in asymptomatic persons with type II diabetes remains controversial. In our study in healthy persons with non-obstructive carotid atherosclerosis negative stress echocardiography, coronary artery calcium was higher and coronary flow velocity reserve was lower in persons with compared to those without type II diabetes. Coronary artery calcium-based 10-year hazard of cardiovascular events was found to be as high as 10–20%, or above 20%, in 78% and 11% of the persons with type II diabetes, respectively, as compared to 28% and 0%, respectively, in persons without type II diabetes. Abstract: Aims: To quantify cardiovascular risk in persons with type-2 diabetes (DM) and established carotid atherosclerosis, without inducible myocardial ischemia by stress imaging. Methods: We selected clinically healthy DM and subjects without DM (nonDM, controls) with non-obstructive carotid atherosclerosis and without significant coronary artery disease (CAD) by stress echocardiography. Coronary flow velocity reserve (CFR) was assessed during stress echocardiography. In those with negative stress imaging, coronary artery calcium (CAC) assessment by computed tomography (CT) was proposed. Outcome at 180-day follow-up was performed by visits or telephone interview. Results: Total CAC was greater in DM ( n  = 19) than in nonDM ( n  = 19, CAC: 225 ± 158 vs 78 ± 65 Agatston units, 156 ± 161 vs 53 ± 51 in the left anterior descendent artery, both p  < 0.05). Coronary stenosis burden was greater in DM than in nonDM, albeit <75% in all cases; CFR was lower in DM than nonDM ( p  < 0.05). Mean age was slightly higher (69 ± 6 vs 64 ± 12, p  > 0.2), and male gender tended to be less frequent (63 vs 79%) with DM than with nonDM; all subjects showed dyslipidemia, and almost all had arterial hypertension. Based on CAC, a 10-year cardiovascular risk was 10–20% in 78% of the DM and in 28% of the non-DM, and was >20% in 11% of the DM but in none of the nonDM. A single non-fatal myocardial infarction was recorded within 180 days from test, among DM. Conclusions: Based on CAC, in the presence of non-obstructive carotid atherosclerosis, asymptomatic DM may show significantly higher CAD burden than nonDM even in the absence of inducible myocardial ischemia.